Hydrometallurgical investigations of clean technologies - Lovera Dávila, Daniel Florencio (1999)
A selection of hydrometallurgical applications are shown in the processing of sulfur concentrates, being influenced by environmental regulations; being known as clean technologies. The hydrometallurgy technology of leaching, solvent extraction and electrodeposition is described, as well as a series of current investigations to avoid the production of SO2 through the LIX-SX-EW hydrometallurgical route; as well as solid waste management with arsenic content, for safe storage.